Perancangan Media Pembelajaran Informatika Berbasis Android Menggunakan Smart Apss Creator - Qomaliah Harahap, Indah; Antoni Musril, Hari; Jasmienti, Jasmienti; Derta, Sarwo (Intellect : Indonesian Journal of Learning and Technological Innovation, 2024)
This research is motivated by the students' difficulties in understanding the informatics learning delivered by the teacher because informatics is quite difficult learning, whereas in the learning process teachers still use conventional learning media such as printed books, blackboards and internet sources, the delivery of which is too monotonous, making students feel bored and not enthusiastic about learning. Therefore, valid, practical and effective learning media is needed so that it can support and assist teachers in delivering the informatics learning process at SMPN 1 Bukittinggi. Researchers try to develop Android-based learning media using the smart apps creator application. Research and development (R&D) methods are used. Richey and Klein's development strategy, especially PPE (Planning, Production, and Evaluation). In this research, researchers conducted three product tests, namely a validity test from two expert lecturers and 3 teachers with an average validity value of 0.92 in the valid category, a practicality test from 2 teachers with a value of 0.844 in the high category and an effectiveness test by 1 teacher and 10 students, an average score of 0.89 was obtained in the effective category, so that Android-based informatics learning media using the Smart Apps Creator application is feasible and can be used. Abstrak Penelitian ini dilatarbelakangi tentang kesulitan siswa dalam memahami pembelajaran informatika yang disampaikan oleh guru dikarenakan informatika sebagai pembelajaran yang cukup sulit sedangkan dalam proses pembelajaran guru masih menggunakan media pembelajaran konvensional seperti penggunaan buku cetak, papan tulis dan sumber dari internet yang penyampaiannya terlalu monoton sehingga membuat siswa merasa bosan dan tidak bergairah untuk mengikuti pembelajaran. Oleh karena itu diperlukan media pembelajaran yang valid, praktis dan efektif agar dapat mendukung dan membantu guru dalam menyampaikan proses pembelajaran informatika di SMPN 1 Bukittinggi. Peneliti mencoba mengembangkan media pembelajaran berbasis android menggunakan aplikasi smart apps creator. Metode penelitian dan pengembangan (R&D) digunakan. Strategi pengembangan Richey dan Klein khususnya PPE (Planning, Production, and Evaluation). Produk media yang dirancang dilakukan proses pengujian yaitu uji validitas dari dua orang dosen ahli dan 3 orang guru  dengan nilai rata-rata validitas sebesar 0,92 dengan kategori valid, uji praktikalitas dari 2 orang guru dengan nilai 0,844 dengan kategori tinggi dan uji efektivitas oleh 1 orang guru dan 10 orang siswa diperoleh nilai rata-rata 0,89 dengan  kategori efektif, sehingga media pembelajaan informatika berbasis aindroid menggunakan aplikasi smart apps creator layak dan dapat digunakan.